Le système monétaire européen : Où en sommes-nous? - Decaluwé, Bernard (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1981)
The decisions of the Council of Europe on December 5"', 1978, that would lead to the establishment of the European Monetary System, raise a multitude of questions. Among these, the creation of a European currency unit, the ECU, and the announcement of the establishment in the near future of a European Monetary Fund, the E.M.F., are the most symbolic decisions in terms of public opinion as well as the most important in their economic and political implications. In this article, we will show that the development of the ECU and the creation of a E.M.F. with substantial decisional autonomy are the two conditions necessary for strengthening the European monetary union.